Analysis of User Satisfaction Live Shopping of the Shopee Application Using End User Computing Satisfaction (EUCS) and Performance, Information, Economic, Control, Efficiency, and Service (PIECES) Methods: Analisis Kepuasan Pengguna Live Shopping Aplikasi Shopee Menggunakan Metode End User Computing Satisfaction (EUCS) dan Performance, Information, Economic, Control, Efficiency, and Service (PIECES) - Kartikasari, Reyka Ayu; Suyatno, Dwi Fatrianto (Universitas Negeri Surabaya, 2023)
Many companies are competing to add variety to the online buying and selling business, such as offering products by live sellers. One platform that takes advantage of this is Shopee. However, it is known that the use of live shopping of the shopee application itself is still inferior to other similar applications and there are still some complaints or negative reviews. A service can be said to be successful in providing satisfaction if it can meet the needs of its users. The purpose of this study was to determine the results of measuring user satisfaction using the EUCS and PIECES methods, based on 11 variables namely content, accuracy, format, ease of use, timeliness, performance, information, economics, control, efficiency, and service. The data was obtained by distributing research questionnaires to users who made purchases on the Shopee application live shopping in Indonesia and obtained as many as 385 respondents. Based on the analysis conducted, it was found that all variables gave very satisfactory interpretation values ??with the highest value obtained by service at 90.42%, while the lowest value was obtained by timeliness at 78.31%. Then, all of these variables have a simultaneous effect on user satisfaction, whereas if partially all variables have an effect. However, there are two variables that do not have a partial effect, namely timeliness and efficiency.